The Making of a European Constitution
V, 263 p.
Keywords: The aim of this publication is an analysis of the process of European constitutionalisation and its entanglement with relevant national discourses. Thus, national constitutional traditions in Austria, France, Germany and the United Kingdom are evaluated with regard to the positions of the respective national representatives in the European Convention. Interviews with Members of National Parliaments and of the European Parliament as well as a content analysis of the debate on the future of Europe in print media form the empirical basis of this study.